Mission statements for college libraries (College Library Information Packet Committee, College Libraries Section, Association of College and Research Libraries, American Library Association, 1985)
Introduction. Importance of the study ; Objective of the study ; The survey sample and methodology ; Survey results. -- CLIP notes survey (Results) -- 1975 "Standards for college libraries" -- The mission of the undergraduate library (Model statement) -- Mission statements. Private institutions (under 2500 students): Albright College, Albuquerque, University of, Capital University, Carleton College, Denison University, Eckerd College, Kalamazoo College, Lake Forest College, Lewis and Clark College, Wheaton College ; Private institutions (2500 students and over): Bucknell University, Butler University, Colgate University, Creighton University, Elon College, Evansville, University of, Loyola University (New Orleans), Manhattanville College, Portland, University of, Pratt Institute, Widener University ; Public institutions (under 2500 students): Northern State University ; Public institutions (2500 students and over): Austin Peay State University, The Citadel, Midwestern State University, Wisconsin-Parkside, University of. -- Regional accreditation agencies' statements. Middle States Association of College and Schools ; New England Association of Schools and Colleges, Inc. ; North Central Association of Schools and Colleges ; Northwest Association of Schools and Colleges ; Southern Association of Schools and Colleges ; Western Association of Schools and Colleges.